Impact of distributed power generation on protection coordination in distribution network - Zineb El Idrissi; Faissal El Mariami; Abdelaziz Belfqih; Touria Haidi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In the whole world and especially in Morocco, the electric power sector faces significant challenges and the demand for energy is increasing as fossil fuel sources are disappearing. Moreover, the high cost of construction of large production plants and the obligation to reduce greenhouse gas emissions are among the factors pushing the energy sector to integrate distributed generators DGs based on renewable energies into power grids. However, the integration of these generators increased the values of short-circuit currents in the network, which poses a real threat to the existing protection coordination systems in the distribution network. The aim of this article is to bring together in a single platform all available research addressing the issue of protection coordination in the presence of DGs in the distribution network, in order to help researchers identify future scope. This paper presents a review of the impact of distributed generators on the protection coordination of distribution networks. The solutions proposed in the literature, to mitigate the negative impact of DGs, have been investigated in detail, along with the limitations of these proposed techniques.